Evaluation of upper extremity ataxia through image processing in individuals with multiple sclerosis - Fatma Erdeo; İbrahim Yildiz; Ali Ulvi Uca; Mustafa Altaş (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Impaired dexterity is a frequently reported disability among people with ataxic multiple sclerosis (MS). Objective: To quantify and standardize the evaluation of upper extremity coordination disorder among patients with multiple sclerosis (MS), using the Tablet Ataxia Assessment Program (TAAP). Methods: The X and Y axis movements of 50 MS patients and 30 healthy individuals who were evaluated using the International Cooperative Ataxia Rating Scale (ICARS) were also assessed using TAAP. The functional times of the participants’ right and left hands were recorded using the nine-hole peg test (NHPT). The upper extremity coordination of individuals with MS was evaluated using the upper extremity kinetic functions section of ICARS. Results: The deviations for the X and Y axis movements of the MS group were greater than those of the control group (p<0.05). Significant correlations were shown between TAAP scores and NHPT and ICARS scores. The strongest correlation was found between NHPT and ICARS in the dominant hand (rnhpt=0.356, pnhpt=0.001; ricars=0.439, picars=0.000). In correlating the Y axis with ICARS, the deviations in the Y axis were found to be greater in the non-dominant hand than those in the X axis (ryright=0.402, pyright=0.004; ryleft=0.691, pyleft=0.000). Conclusion: Measurement using TAAP is more sensitive than other classical and current methods for evaluating ataxia. We think that TAAP is an objective tool that will allow neurorehabilitation professionals and clinicians to evaluate upper extremity coordination.